METHODOLOGICAL ASPECTS OF RESEARCH ORTHODOX ANTHROPOLOGY - Stetzuk, R. V. (Anthropological Measurements of Philosophical Research, 2012)
The article analyzes the approaches to the Orthodox anthropology that existed and exist both in philosophical and theological studies and in theology. Three areas in the study of Orthodox anthropology.